Synthesis of novel multifunctional carbazole-based molecules and their thermal, electrochemical and optical properties - Altinolcek, Nuray; Battal, Ahmet; Tavasli, Mustafa; Peveler, William J.; Yu, Holly A.; Skabara, Peter J. (Beilstein Journal of Organic Chemistry, 2020)
Two novel carbazole-based compounds 7a and 7b were synthesised as potential candidates for application in organic electronics. The materials were fully characterised by NMR spectroscopy, mass spectrometry, FTIR, thermogravimetric analysis, differential scanning calorimetry, cyclic voltammetry, and absorption and emission spectroscopy. Compounds 7a and 7b, both of which were amorphous solids, were stable up to 291 °C and 307 °C, respectively. Compounds 7a and 7b show three distinctive absorption bands: high and mid energy bands due to locally excited (LE) transitions and low energy bands due to intramolecular charge transfer (ICT) transitions. In dichloromethane solutions compounds 7a and 7b gave emission maxima at 561 nm and 482 nm with quantum efficiencies of 5.4% and 97.4% ± 10%, respectively. At positive potential, compounds 7a and 7b gave two different oxidation peaks, respectively: quasi-reversible at 0.55 V and 0.71 V, and reversible at 0.84 V and 0.99 V. At negative potentials, compounds 7a and 7b only exhibited an irreversible reduction peak at −1.86 V and −1.93 V, respectively.
Keywords: carbazole; electrochemistry; fluorescence; formyl group; solvatochromism